Can Investors Depend only on Accounting Information in Investment Decision-Making? - Badshah, Imtiaz; Khan, Muhammad Ibrahim; Khattak, Amira; Jalil, Zunaira; Gul, Seema (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to understand and analyse the investor’s behaviour in investment decision-making in relation to factors other than quantitative ratios. This study is therefore the first of its kind to adopt qualitative method such as an interview guide for collecting data on behavioural factors that may affect the investor’s investment decision-making. In total eight detailed interviews were conducted, five with individual and three with institutional investors in Pakistan. Behavioural factors affecting investors’ investment decision-making were identified as heuristic biases (such as representativeness, availability, anchoring and overconfidence) and herding behaviour, with the main focus on the former. This research affirmed the presence of heuristic biases and a herding approach among Pakistani investors in relation to investment-related decisions. Interestingly, all four types of heuristic behaviour – representativeness, anchoring, overconfidence and availability bias – are reported among Pakistani investors based on their responses to the questions.